METHODS FOR DEVELOPING FORMAL SPEAKING SKILLS IN ENGLISH - Alimardonova Maftuna Bekmurodovna (Journals Park Publishing, 2024)
This article examines various strategies for improving formal speaking skills in English, crucial for success in professional and academic settings. It explores methods such as structured speaking activities, pronunciation practice, vocabulary expansion, and speech organization techniques, highlighting their importance in fostering clarity and confidence in formal communication.
Keywords: formal speaking, English, development, strategies, proficiency, communication, skills.